(untitled) (Research, Society and Development, 2021)
Currently, the high incidence of dengue is related to structural inequality and the lack of basic sanitation found in various precarious environments, in which families live in susceptible situations. This work aims to analyze the occurrence of dengue cases in the period from 2015 to 2020, as well as to determine an association of how socioeconomic factors such as inadequate housing, minimum income, family agglomerations, household densities and the lack of basic sanitation, have potential to influence the spread of the disease. This study aimed to present a systematic review of previously published academic papers on the focus of dengue in people’s lives and the danger it poses to the population. The results found showed a positive incidence in the correlation with the social factors mentioned, thus favoring the proliferation of Aedes aegypti.